2021
DOI: 10.1007/s00425-021-03684-3
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the complete mitochondrial genome of an endemic plant, Scutellaria tsinyunensis, revealed the existence of two conformations generated by a repeat-mediated recombination

Abstract: Main conclusionWe assembled the complete mitochondrial genome of Scutellaria tsinyunensis in this study. Repeatmediated recombination resulted in the formation of two conformations of the mitochondrial genome in S. tsinyunensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 72 publications
10
34
0
Order By: Relevance
“…The long repeats we found in the okra mitochondrial genome also have a high frequency of recombination. For short repeats, they all had low recombination frequency, which is consistent with those previously reported [ 28 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…The long repeats we found in the okra mitochondrial genome also have a high frequency of recombination. For short repeats, they all had low recombination frequency, which is consistent with those previously reported [ 28 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…For large repeats, such as the typical inverted repeats observed in chloroplast DNA (cp DNA), it was previously thought that equal proportions mediate SSC region recombination [ 57 ]. Here, all of the repeats identified in the mitogenome of plum are short repeats, and they all have low recombination frequency, which are findings that are consistent with those previously reported [ 49 , 50 ]. However, organelles tend to have high copy numbers.…”
Section: Discussionsupporting
confidence: 92%
“…However, 182 long reads supported the master circle conformation, suggesting a lower frequency of recombination. As for the remaining repeats, they recombined the mitogenome at a lower frequency, similar to the results previously observed in Scutellaria tsinyunensis and Nymphaea colorata [ 49 , 50 ], namely that the configuration of the master circle was overwhelmingly dominant in the mitochondrion. Our results also support previous studies that showed that the frequency of recombination mediated by short repeats tends to be lower than that mediated by long repeats, with the isomers mediated by this being closer to equal proportions.…”
Section: Resultssupporting
confidence: 81%
“…It has been reported that the size of the repeats is closely related to the frequency of recombination [ 63 ]; namely, the frequency of recombination mediated by short repeats tends to be lower than that mediated by long repeats. For example, in Nymphaea colorata Peter [ 64 ], Scutellaria tsinyunensis C. Y. Wu et S. Chow [ 65 ] and Abelmoschus esculentus (L.) Moench [ 66 ], the long repeats had high recombination frequencies, and the short repeats had lower recombination frequencies; all of the repeats identified in the Prunus salicina Lindl. [ 67 ] mitogenome were short repeats, and they all had low recombination frequency.…”
Section: Discussionmentioning
confidence: 99%